Proteasome impairment by α-synuclein - Zondler, Lisa; Kostka, Marcus; Garidel, Patrick; Heinzelmann, Udo; Hengerer, Bastian; Mayer, Benjamin; Weishaupt, Jochen H.; Gillardon, Frank; Danzer, Karin M. (PLOS ONE, 2017)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disorder worldwide and characterized by the loss of dopaminergic neurons in the patients’ midbrains. Both the presence of the protein α-synuclein in intracellular protein aggregates in surviving neurons and the genetic linking of the α-synuclein encoding gene point towards a major role of α-synuclein in PD etiology. The exact pathogenic mechanisms of PD development are not entirely described to date, neither is the specific role of α-synuclein in this context. Previous studies indicate that one aspect of α-synuclein-related cellular toxicity might be direct proteasome impairment. The 20/26S proteasomal machinery is an important instrument of intracellular protein degradation. Thus, direct proteasome impairment by α-synuclein might explain or at least contribute to the formation of intracellular protein aggregates. Therefore this study investigates direct proteasomal impairment by α-synuclein both in vitro using recombinant α-synuclein and isolated proteasomes as well as in living cells. Our experiments demonstrate that the impairment of proteasome activity by α-synuclein is highly dependent upon the cellular background and origin. We show that recombinant α-synuclein oligomers and fibrils scarcely affect 20S proteasome function in vitro, neither does transient α-synuclein expression in U2OS ps 2042 (Ubi(G76V)-GFP) cells. However, stable expression of both wild-type and mutant α-synuclein in dopaminergic SH-SY5Y and PC12 cells results in a prominent impairment of the chymotrypsin-like 20S/26S proteasomal protein cleavage. Thus, our results support the idea that α-synuclein in a specific cellular environment, potentially present in dopaminergic cells, cannot be processed by the proteasome and thus contributes to a selective vulnerability of dopaminergic cells to α-synuclein pathology.